Dosimetric characterization of DSF/NaOH/IA-PAE/R. spp. phantom material for radiation therapy - Samson, Damilola Oluwafemi; Shukri, Ahmad; Ab. Aziz, Nurul Hashikin; Zuber, Siti Hajar; Abdul Aziz, Mohd Zahri; Hashim, Rokiah; Mohd Yusof, Mohd Fahmi; Rabaiee, Nor Ain; Gemaman, Sylvester Jande (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Background: Different compositions of DSF/NaOH/IA-PAE/R. spp. composite particleboard phantoms were constructed. Methods: Photon attenuation characteristics were ascertained using gamma rays from 137Cs and 60Co. Absorbed doses at the location of an ionization chamber and Gafchromic EBT3 radiochromic films were calculated for high-energy photons (6 and 10 MV) and electrons (6, 9, 12, and 15 MeV). Results: The calculated TPR20,10 values indicate that the percentage discrepancy for 6 and 10 MV was in the range of 0.29–0.72% and 0.26–0.65%. It was also found that the relative difference in the dmax to water and solid water phantoms was between 1.08–1.28% and 5.42–6.70%. The discrepancies in the determination of PDD curves with 6, 9, 12, and 15 MeV, and those of water and solid water phantoms, ranged from 2.40–4.84%. Comparable results were found using the EBT3 films with variations of 2.0–7.0% for 6 and 10 MV photons. Likewise, the discrepancies for 6, 9, 12, and 15 MeV electrons were within an acceptable range of 2.0–4.5%. Conclusions: On the basis of these findings, the DSF/NaOH/IA-PAE/R. spp. particleboard phantoms with 15 wt% IA-PAE addition level can be effectively used as alternative tissue-equivalent phantom material for radiation therapy applications.